Accuracy of the Tentative Underlying Cause of Death Code Based on Rule 1 And Rule 2 - Widyaningrum, Linda; Yuliadi, Naufal Arifin; Sari, Sella Yulia (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Tentative Underlying Cause of Death (TUCoD) is the code selected as the result of each step in the process, when applying the instructions for each step. This research is a descriptive study with a cross sectional data approach, data sources obtained from primary data, namely the results of patient medical record documents and the results of interviews with the head of medical records and coding officers using research instruments, observation guidelines, interview guidelines, check-lists, MMDS tables. The samples taken was 82 samples from a total population of 444 general death certificates. The data sources taken are primary sources, namely the results of interviews and observations and secondary sources are taken from the SPO for coding the death index. The results of the accuracy of writing the sequence of events were 85% and the inaccuracy was 15%, this was due to the recording being carried out by the doctor in charge of the patient, determination of the tentative underlying cause of death code which is based on rule 1 at 24% with each rule 1 namely Rule 1.1 at 45% and rule 1.2 at 55%, rule 2 is 7% and General Principle rule is 69. Conclution this researsch procedure uses ICD-10 but does not involve MMDS, 85% of the event sequence writing is accurate, while 15% is inaccurate, the determination of rule 1 is 26% respectively for rule 1, namely rule 1.1 at 43% and rule 1.2 at 57% rule 2 at 6% and rule GP at 68% suggest immediate revision of the SOP for causes of death by involving MMDS in the death coding procedure. It would be better for coding officers to be more careful in coding the diagnosis of the basic cause of death so that there is no diagnosis without a code. diagnosis and improve coordination between medical record officers, doctors and other health workers to increase the completeness of medical records.